2019
DOI: 10.3390/ijms20225545
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-Phosphate (S1P)/ S1P Receptor Signaling and Mechanotransduction: Implications for Intrinsic Tissue Repair/Regeneration

Abstract: Tissue damage, irrespective from the underlying etiology, destroys tissue structure and, eventually, function. In attempt to achieve a morpho-functional recover of the damaged tissue, reparative/regenerative processes start in those tissues endowed with regenerative potential, mainly mediated by activated resident stem cells. These cells reside in a specialized niche that includes different components, cells and surrounding extracellular matrix (ECM), which, reciprocally interacting with stem cells, direct the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 276 publications
(377 reference statements)
0
30
0
Order By: Relevance
“…Prominent examples involved in tissue regeneration and mechanosensing/mechanotransduction in bone and muscle are prostaglandins, NO, sphingosines, and ATP, and its dephosphorylation-related products that fuel into purinergic signaling. Physical forces through muscular activity or vibration induce the cellular secretion of ATP and sphingosines, which are tightly involved in osteoblast, osteoclast, and osteocyte activity [2,[63][64][65].…”
Section: Secretion and Autocrine/paracrine/endocrine Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Prominent examples involved in tissue regeneration and mechanosensing/mechanotransduction in bone and muscle are prostaglandins, NO, sphingosines, and ATP, and its dephosphorylation-related products that fuel into purinergic signaling. Physical forces through muscular activity or vibration induce the cellular secretion of ATP and sphingosines, which are tightly involved in osteoblast, osteoclast, and osteocyte activity [2,[63][64][65].…”
Section: Secretion and Autocrine/paracrine/endocrine Communicationmentioning
confidence: 99%
“…Finally, besides SLIT3, also other axon-guided molecules such as semaphorin-4D (SEMA4D), SEMA3A, and netrin-1 were described to couple osteoblast and osteoclast activity in the remodeling process (coupling reviewed in [119]). While the role of such coupling systems in bone remodeling becomes more and more evident, systems such as sphingosine 1-phosphate and its receptor appear to be involved in mechanotransduction not only in development but also in adult life [65,120]. Bone remodeling involves the removal of gratuitous or old and damaged bone by osteoclasts ahead of tissue restoration according to (new) physical strain conditions [118].…”
Section: Principles Of Bone Formation Maintenance and Regenerationmentioning
confidence: 99%
“…In physical conditions, they play contrasting roles within cellular metabolism. Ceramide has been shown to be involved in stress-related cellular responses and apoptosis, whereas S1P stimulates cell survival, proliferation, and tissue regeneration [1][2][3][4]. Hence, maintaining the balance between ceramide and S1P is crucial for cells, as these bioactive lipids substantially contribute to cell fate decisions [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The down-regulation of S1PR1 and S1PR3 also occurs after denervation confirming the trophic action of S1P/S1PR [126]. In an ex-vivo murine model of muscle damage induced by eccentric contraction, the bioactive lipid is able to reduce the deposition of collagen and promote the expression of metalloprotease-9, indicating the ability of S1P to affect the stiffness of the extracellular matrix and then satellite cell behavior [12,127]. In addition, Bondì et al [128] observed that S1P/S1PR3 axis plays a negative role in muscle mass maintenance and force in soleus during aging and extracellular S1P exerts a protective effect during muscle fatigue development [129].…”
Section: S1pr In Skeletal Muscle Systemmentioning
confidence: 75%
“…In addition, Bondì et al [128] observed that S1P/S1PR3 axis plays a negative role in muscle mass maintenance and force in soleus during aging and extracellular S1P exerts a protective effect during muscle fatigue development [129]. S1P/S1PR3 signaling also modulates excitation-contraction coupling and intracellular calcium mobilization [121][122][123][124][125][126][127][128][129][130].…”
Section: S1pr In Skeletal Muscle Systemmentioning
confidence: 99%